Behaviours of Medicago truncatula-Sinorhizobium meliloti symbioses under osmotic stress in relation with the symbiotic partner input: Effects on nodule functioning and protection - Fotopoulos, Vasileios; Mhadhbi, Haythem; Djebali, Naceur (My University, 2009)
Three genotypes of the model legume Medicago truncatula were assessed for symbiotic effectiveness in cross inoculation with two strains of Sinorhizobium meliloti under mannitol-mediated osmotic stress. Symbioses showed different tolerance levels revealed on plant growth, nitrogen-fixing capacity and indices of nodule functioning and protection. The variability of stress response was essentially correlated with performance at non-stressful conditions. Symbiosis attitude depended on bacterial partner, host-plant genotype and their interaction. Plant genotype manifested the highest contribution to symbiotic efficiency indices under osmotic stress, even for nodulation and nitrogen fixation where the bacterial strain effect is highly pronounced. Contrasting (tolerant/sensitive) associations were identified for tolerance behaviours, involving the same plant genotype with different rhizobial strains and vice versa. In nodules, osmotic stress leads to accumulation of oxidized lipids and decrease in total protein and leghaemoglobin contents. Antioxidant responses were manifested as induction of guaiacol peroxidase (POX, E.C. 1.11.1.7) and superoxide dismutase (E.C. 1.15.1.1). POX induction was higher in tolerant symbioses and both enzymes were suggested as contributors to the protection of nodule integrity and functioning under osmotic stress. In conclusion, symbiotic efficiency in M. truncatula-S. meliloti combinations under osmotic stress is determined by each symbiont's input as well as the plant-microbe genotype interaction, and POX induction could prove a sensitive marker of tolerant symbioses
Keywords: Toleration; Antioxidants; Inoculation; Nitrogen--Fixation; Osmosis; Proteins; Symbiosis; Toleration; Bacteria